The key role of Au-substrate interactions in catalytic gold subnanoclusters - Jesús Cordón (Nature Portfolio, 2017)
Stabilization of gold nanoclusters in order to prevent their self-aggregation remains a great challenge. Here, the authors describe transient stabilization of very small catalytic gold subnanoclusters by alkyl chains or aromatic groups appended to the reactive π bond of simple alkynes.